INCLUSIVE EDUCATION TRANSFORMATION: IMPROVING STUDENTS' SOCIAL WELFARE AMIDST DYNAMIC GLOBAL CHANGES IN ISLAMIC EDUCATION INSTITUTIONS - Junaedi, Acmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education has become a critical focal point in the context of global educational reforms, aiming to address diverse student needs and promote social equity. This paper explores the transformation of inclusive education and its role in enhancing student social well-being amidst dynamic global changes. As the world rapidly evolves through technological advancements, socio-economic shifts, and cultural integration, education systems are challenged to adapt and provide equal opportunities for all students, including those with disabilities, learning difficulties, and other marginalized groups. The dynamic nature of these changes, however, has sparked both opportunities and controversies regarding the implementation and effectiveness of inclusive education practices. This study examines the various dimensions of inclusive education, including policy frameworks, teaching methodologies, and the socio-cultural impact on students’ well-being. It analyzes how global changes, such as the digital divide, economic disparities, and cultural globalization, influence the success of inclusive education initiatives. Furthermore, it discusses the role of inclusive education in fostering social integration, promoting empathy, and supporting the holistic development of students in diverse learning environments. The paper concludes by emphasizing the need for continuous dialogue among educators, policymakers, and communities to ensure the effective transformation of inclusive education. A comprehensive approach to addressing the challenges and embracing the potential of inclusive education is essential for enhancing the social well-being of students and achieving a more equitable and sustainable educational future in the face of global change. Keywords: Inclusive Education, Social Welfare, Educational Transformation, Equality, Diversity